Recommendations for studies on dynamic arm support devices in people with neuromuscular disorders: a scoping review with expert-based discussion. (4th July 2022) - Essers, J. M. N.; Murgia, A.; Peters, A. A.; Janssen, M. M. H. P.; Meijer, K.
Abstract: Purpose: Neuromuscular disorders are characterised by muscle weakness that limits upper extremity mobility, but can be alleviated with dynamic arm support devices. Current research highlights the importance and difficulties of evidence-based recommendations for device development. We aim to provide research recommendations primarily concerning upper extremity body functions, and secondarily activity and participation, environmental and personal factors. Methods: Evidence was synthesised from literature, ongoing studies, and expert opinions and tabulated within a framework based on a combination of the International Classification of Functioning, Disability and Health (ICF) model and contextual constructs. Results: Current literature mostly investigated the motor capacity of muscle function, joint mobility, and upper body functionality, and a few studies also addressed the impact on activity and participation. In addition, experts considered knowledge on device utilisation in the daily environment and characterising the beneficiaries better as important. Knowledge gaps showed that ICF model components and contextual constructs should be better integrated and more actively included in future research. Conclusions: It is recommended to, first, integrate multiple ICF model components and contextual constructs within one study design. Second, include the influence of environmental and personal factors when developing and deploying a device. Third, include short-term and long-term measurements to monitor adaptations over time. Finally, include user satisfaction as guidance to evaluate the device effectiveness. IMPLICATIONS ON REHABILITATION: Synthesized evidence will support future research and development of dynamic arm supports. Tabulated evidence stresses the importance of integrating ICF model components and contextual constructs to fill the knowledge gaps. Presented knowledge gaps and proposed steps guide the set up of future studies on dynamic arm supports